2023
DOI: 10.1080/17461391.2023.2171907
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Nike ZoomX Vaporfly Next% 2 shoe on long‐interval training performance, kinematics, neuromuscular parameters, running power and fatigue

Abstract: We analysed the effects of the Nike ZoomX Vaporfly (VPF) on long-interval training performance, kinematic parameters, running power and fatigue compared to a traditional running shoe. Twelve well-trained men (mean ± SD: 32.91 ± 7.50 years; 69.29 ± 7.55 kg and 172.73 ± 5.97 cm) performed two long-interval training sessions (5 × 1000 m with 90s recovery period) 7 days apart, with the VPF shoe or a traditional running shoe (CON) in random order. The countermovement jump (CMJ) height was measured before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…Nike used digital consumption to a large extent to meet the security needs of consumers, based on the consumer payment choice model, consumers prefer to pay in cash, not only because cash is commonly accepted, but also because cash payments are the safest form of payment because there is no risk or technical failure. However, in the broader context of COVID-19, consumers' perceived risk levels can significantly increase [7]. Digital payments can be made easily and quickly, anywhere and anytime.…”
Section: Security Requirementsmentioning
confidence: 99%
“…Nike used digital consumption to a large extent to meet the security needs of consumers, based on the consumer payment choice model, consumers prefer to pay in cash, not only because cash is commonly accepted, but also because cash payments are the safest form of payment because there is no risk or technical failure. However, in the broader context of COVID-19, consumers' perceived risk levels can significantly increase [7]. Digital payments can be made easily and quickly, anywhere and anytime.…”
Section: Security Requirementsmentioning
confidence: 99%
“…This paper will provide physical fitness guidance for special groups, strengthen nonmedical and health intervention, establish and improve exercise prescription databases, and promote the application of prescriptions. In fact, since the success of the 2008 Olympic Games, the concept of national health has been quickly formed, forming a wave of sports boom across the country, and the government is also vigorously supporting and supporting the cause of sports [2]. In 2009, the state passed the National People's Physical Health Day, and the Comprehensive Fitness Regulations also took effect on October 1, which clearly stated that all relevant departments should strengthen the publicity of national health knowledge and organize the masses to participate in sports activities.…”
Section: Policy Environmentmentioning
confidence: 99%
“…For AFT shoes, previous studies have reported greater RE improvements in highly trained/national runners (sub-32:00 men and 35:30 women for 10 km) (2)(3)(4) than in recreational/ trained runners (~45:00 for 10 km) (5,(18)(19)(20). A recent meta-analysis showed a RE improvement in world-class and amateur runners with the greatest variability of results in the world-class runners (21).…”
mentioning
confidence: 97%